2018
DOI: 10.1017/s1368980018003336
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the factors influencing low-income caregivers’ perceived value of a federal nutrition programme, the Special Supplemental Nutrition Program for Women, Infants and Children (WIC)

Abstract: ObjectiveRetention of participants has been an issue in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). It has been suggested that the perceived value of WIC may affect whether participants remain in the programme. The present study aimed to explore this phenomenon.DesignUsing a constructivist approach, thirty-one individual in-depth interviews were conducted. Transcripts were analysed using constant comparative analysis. Social, cultural and environmental factors that contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…Bensley et al also demonstrated that WIC participants would find universal product code (UPC) scanning and verification of WIC items useful (5782/8144, 71%) [ 20 ]. Issues at checkout and conflicting information regarding WIC item eligibility remains a barrier to using WIC [ 13 ] and is one of the key factors that decrease participants’ perceived value of the program [ 14 ]. A barcode scanning feature to verify item eligibility and confirm whether or an item remains on the WIC balance could provide a solution to this common barrier to redeem WIC benefits.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Bensley et al also demonstrated that WIC participants would find universal product code (UPC) scanning and verification of WIC items useful (5782/8144, 71%) [ 20 ]. Issues at checkout and conflicting information regarding WIC item eligibility remains a barrier to using WIC [ 13 ] and is one of the key factors that decrease participants’ perceived value of the program [ 14 ]. A barcode scanning feature to verify item eligibility and confirm whether or an item remains on the WIC balance could provide a solution to this common barrier to redeem WIC benefits.…”
Section: Discussionmentioning
confidence: 99%
“…A semistructured interview protocol was developed based on a multilevel model of factors influencing the perceived value of WIC [ 14 ], as well as formative research [ 28 ] and a review of existing WIC apps and features [ 27 ]. Using the semistructured interview protocol, participants were asked to speak about their experiences using WIC services, shopping for WIC foods, and using mobile phone technology.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the shopping level, WIC state agencies were mandated to switch from a paper voucher system to an electronic benefits transfer (EBT) system for WIC by 2020, with some waivers of extension [23] in which participants make WIC purchases using an EBT card that resembles a debit card. Implementation of WIC EBT (or electronic WIC [eWIC]), as many state agencies refer to it) is a considerably large administrative undertaking that stands to benefit participants considerably owing to increased ease of use at checkout, elimination of the risk of theft or loss of paper vouchers, increased redemption of benefits, and decreased stigma associated with purchasing food using a discreet benefit card rather than cumbersome paper vouchers that can cause difficulties for customers and cashiers [14,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%